What Determine the Organizational Citizenship Behavior in Indonesian Agriculture Manufacturing Firms? - Siriattakul, Parinya; Jermsittiparsert, Kittisak; Mustanir, Ahmad (International Journal of Psychosocial Rehabilitation, 2019)
The main purpose of the current study is to investigate the determine the organizational citizenship behavior in Indonesian agriculture manufacturing firms. Total 670 questionnaires were distributed among the agricultural manufacturing firms of Indonesia. The response rate was very good due to which a total of 470 questionnaires have been received, with a response rate of 71%.The study has used the SEM-PLS as the statistical technique to answer the research questions. Furthermore, the study used this technique primarily because this paper aims to assess whether these variables have any mediating effect on the relationships. The other reason is that this technique of PLS path modeling is compatible with the normal as well as non-normal data. Most social science researches exhibit non-normality of data. Therefore, PLS is suitable for these kinds of researches, as it can easily handle the data abnormality. Another significant feature of PLS path modeling is its proficiency in simultaneously estimating the measurement and the structural model. The response rate of the study is 71 percent, which is considerably higher. The study is among the pioneering study on the issue and will be helpful for the policymakers and researchers